2020
DOI: 10.3389/fvets.2020.00089
|View full text |Cite
|
Sign up to set email alerts
|

Owner and Veterinarian Perceptions About Use of a Canine Quality of Life Survey in Primary Care Settings

Abstract: This paper describes dog owner and veterinarian perceptions around the use of a validated canine quality of life (QOL) survey to facilitate wellness conversations in two clinical settings: a veterinary teaching hospital (pilot, Phase 1) and five corporate general practice hospitals (Phase 2). Phase 1 results showed that dog owners felt the survey was valuable for understanding their dog's QOL, with 81% of owners expressing interest in learning more about canine QOL. Phase 2 reinforced owner perceptions about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…These may include replacing paper‐based forms with digitized OROMs; the development of user‐friendly digital platforms (such as centralized databases and cloud applications) that can be integrated into the existing electronic medical record systems and facilitate the delivery, storage, processing, access, and visualization of OROMs; adequate training to the owners and veterinarians on understanding OROMs and their purpose; and better education of veterinarians on how to communicate the results to owners and how to use OROMs to engage owners in the consultation 3 . An example of educating veterinarians on how to use OROMs can be found in the study by Mwacalimba et al, where the veterinarians were provided with a one‐page guidance document that explained the purpose of the QoL assessment and provided talking points for introducing and explaining the assessment results to owners 5 . These improved the usability of the QoL assessment and resulted in favorable acceptance from the veterinarians.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These may include replacing paper‐based forms with digitized OROMs; the development of user‐friendly digital platforms (such as centralized databases and cloud applications) that can be integrated into the existing electronic medical record systems and facilitate the delivery, storage, processing, access, and visualization of OROMs; adequate training to the owners and veterinarians on understanding OROMs and their purpose; and better education of veterinarians on how to communicate the results to owners and how to use OROMs to engage owners in the consultation 3 . An example of educating veterinarians on how to use OROMs can be found in the study by Mwacalimba et al, where the veterinarians were provided with a one‐page guidance document that explained the purpose of the QoL assessment and provided talking points for introducing and explaining the assessment results to owners 5 . These improved the usability of the QoL assessment and resulted in favorable acceptance from the veterinarians.…”
Section: Discussionmentioning
confidence: 99%
“…Improving patient outcomes should be the ultimate goal for patient care, both in humans and animals 2 . Owner (observer)‐reported outcome measures (OROMs) are validated questionnaires that provide semiquantitative scores based on the subjective evaluation of companion animals' health, function, and/or QoL by their owners/carers 5 . Outcomes from the perspective of the animal's owner/carer are increasingly incorporated in evidence‐based veterinary studies through the use OROMs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After completing the questionnaire, several participating owners found the tool encouraged them to think about and subsequently improve their dog's QoL. Similarly, Mwacalimba et al [2] found a canine QoL survey to be of value in a primary veterinary clinic, with 81% of pet owners expressing interest in learning about QoL.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the intense human-animal bond, pets are often considered valued and respected members of the family [1,2]. Throughout an animal's life, a variety of health issues and medical conditions may develop requiring appropriate treatment or palliative care where necessary.…”
Section: Introductionmentioning
confidence: 99%